Writing and holiness : the practice of authorship in the early Christian East - Krueger, Derek (Divinations., 2004)
Drawing on comparative literature, ritual and performance studies, and the history of asceticism, Derek Krueger explores how early Christian writers came to view writing as salvific, as worship through the production of art.